2021
DOI: 10.3390/admsci11040152
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cultural Capital on Development of Entrepreneurship in Wales

Abstract: The focus of this paper is the impact of parental cultural capital on offspring’s occupational choice in relation to entrepreneurship. Despite growing interest to cultural motives for entrepreneurship on an individual level, few studies link these two domains empirically. This study follows the Culture Based Development research paradigm (CBD) developed by Tubadji and explores how culture influences occupational choices of school graduates during school-to-work transition. The main hypothesis of this paper is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 98 publications
(147 reference statements)
0
1
0
Order By: Relevance
“…Cultural capital is transferred from parents to children through social class, profession, and wealth or power [24]. She also mentions that according to Bourdieu's foundation in 1986, there are three ways to obtain cultural capital: objectified (through works of art, books), institutionalized (educational instruction, study notes, professional career) and embodied (in tastes, language and behaviors, etc.…”
Section: 1b Cultural Capitalmentioning
confidence: 99%
“…Cultural capital is transferred from parents to children through social class, profession, and wealth or power [24]. She also mentions that according to Bourdieu's foundation in 1986, there are three ways to obtain cultural capital: objectified (through works of art, books), institutionalized (educational instruction, study notes, professional career) and embodied (in tastes, language and behaviors, etc.…”
Section: 1b Cultural Capitalmentioning
confidence: 99%
“…Only by clarifying this mechanism can we determine the means of the gradual development from possible root causes and preconditions to the improvement of entrepreneurship competence. Nevertheless, via a literature search, it has been found that there are few discussions on the antecedent variables and influencing factors of entrepreneurship competence [12].…”
Section: Introductionmentioning
confidence: 99%